Translating Catullus 85: why and how - D’Angour, Armand (Philologia Classica, 2019)
This article argues that in the first verse of Catullus’ epigram 85, the commonly found translation of quare as ‘why’ in English versions since the 17th century, but particularly in translations produced in the last fifty years, cannot be accepted. In the context of Catullus’s poetry, with poems 72 and 75 offering an explicit background to and rationale for the contradiction in the poet’s feelings between love and hate, and in the light of the incontrovertible connotation of quare (or qua re) as ‘how’ in a passage of Terence’s Eunuchus, the correct translation of the word can only be ‘how’. Some suggestions are made to account for the origins and the persistence of the mistranslation. The translation as ‘why’ in the prose version in the 1912 Loeb edition edited by F. W. Cornish is suggested to have influenced a generation of English-speaking students, and Martial’s epigram 1.32 is invoked as a cause. But it is further argued that in taking Catullus’s epigram as a model for his own, Martial may have expressly intended to suggest that the meaning of quare as ‘why’ that was current in his time was different in that very respect from the connotation ‘how’ clearly intended by his predecessor.